Urgensi Regulasi Terhadap Penyalahgunaan Deepfake Berbasis Ai (Artificial Intelligence) Pada Konten Pornografi - Seveney, Madalaine Christella; Wicaksono, Demas Brian; Soetijono, Irwan Kurniawan (Disiplin : Majalah Civitas Akademika Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2025)
Technological advances are now growing rapidly, one of which is the emergence of artificial intelligence or what we know as Artificial Intelligence which can automatically quickly carry out human commands to do things and can replace human work. Deepfake is a form of Artificial Intelligence that is proof of technological progress. Deepfake can produce realistic-looking manipulations of fake images, videos, and audio recordings. Deepfake raises new legal challenges in the world of cyber crime in Indonesia, which is often misused for various crimes to violate privacy through pornography. This journal will examine the existing legal regulations in Indonesia in terms of Law No. 44 of 2008 concerning Pornography and Law No. 11 of 2008 concerning Information and Electronics in solving the problem of misuse of Artificial Intelligence-based deepfake on pornographic content. This journal is written using the normative juridical method to find rules, principles, and legal theories to solve the legal problem itself. By using the statutory approach method (Statue approach) and Comparative approach. The conclusion of this research is that until now Indonesia does not have special regulations governing deepfake or other results from Artificial Intelligence which specifically regulate the abuse caused to the manipulation of pornographic content so that there is a need for special regulations related to this problem